Reproductive biology of Triportheus trifurcatus (Castelnau, 1855) (Characiformes: Characidae) in the middle rio Araguaia, MT, Brazil - Martins-Queiroz,Mirian F. (2008)
The study of the reproductive biology of Triportheus trifurcatus of the middle rio Araguaia was carried out using 275 specimens obtained in seven collections conducted in the period between November 2003 and January 2005. Females prevailed among the classes of intermediate length, as well as in the total number of samples. On the other hand, males prevailed in the smaller classes. The average length of females was larger than that of males. Four stages of gonadal maturation were macro- and microscopically identified: B - maturation, C - mature, D - spent and E - resting. Stage A (immature) was not found in the habitats sampled. The smallest-length male was 110 mm in standard length, and the smallest female, 119 mm. The spawning period occurred from November to January, with reproductive peak in December/January, coinciding with the highest water levels. The absolute fecundity is considered low, and there is a positive correlation between fecundity and gonad weight, body weight and standard length. Food ingestion during the reproductive period did not suffer any interference, and it is suggested complete spawning for this species.